2021
DOI: 10.3389/fimmu.2021.725447
|View full text |Cite
|
Sign up to set email alerts
|

Serum Biomarker Profile Including CCL1, CXCL10, VEGF, and Adenosine Deaminase Activity Distinguishes Active From Remotely Acquired Latent Tuberculosis

Abstract: IntroductionThere is an urgent medical need to differentiate active tuberculosis (ATB) from latent tuberculosis infection (LTBI) and prevent undertreatment and overtreatment. The aim of this study was to identify biomarker profiles that may support the differentiation between ATB and LTBI and to validate these signatures.Materials and MethodsThe discovery cohort included adult individuals classified in four groups: ATB (n = 20), LTBI without prophylaxis (untreated LTBI; n = 20), LTBI after completion of prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 62 publications
1
30
0
Order By: Relevance
“…VEGFA, IL6, and IFN-gamma were identified in at least two other proteomic studies (29-33), while CD274 (also called PD-L1) was observed in several published transcriptional signatures. IP-10 (also called CXCL10), which was removed due to its high expression in severe viral LRT and sarcoidosis appears in several proteomic studies (30-33). The other markers were less common or identified in the current study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…VEGFA, IL6, and IFN-gamma were identified in at least two other proteomic studies (29-33), while CD274 (also called PD-L1) was observed in several published transcriptional signatures. IP-10 (also called CXCL10), which was removed due to its high expression in severe viral LRT and sarcoidosis appears in several proteomic studies (30-33). The other markers were less common or identified in the current study.…”
Section: Resultsmentioning
confidence: 99%
“…VEGF was also included in a 4-protein signature (CCL1, CXCL10, ADA-2, VEGF) proposed by Delemarre et al (30), where they compared active TB to treated and untreated latent TB. The signature was validated in two separate patient cohorts with a sensitivity of 95% and a specificity of 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivities achieved with these combinations are similar to those reported in a few other studies aiming to define combinations of biomarkers that provide diagnostic test accuracy consistent with WHO specifications for a rule-out test for aTB. These studies that were recently summarized ( 25 ), are based on combinations of various serum markers, mostly cytokines/chemokines ( 26 28 ), sometimes combined with antibodies against a TB antigen to raise the specificity for TB ( 29 ). We chose in our study to measure cytokines/chemokines released in response to mycobacterial antigens to increase the specificity for TB.…”
Section: Discussionmentioning
confidence: 99%
“…ADA2 is highly expressed in myeloid cells and produced by activated monocytes, macrophages, and DC in the sites of inflammation and TME [81]. Besides, ADA2 is secreted by monocytes during differentiation into macrophages or DC, and its secretion is regulated by interferon (IFN)-γ. Immune-inflammatory diseases such as systemic lupus erythematosis, rheumatoid arthritis, Chrone's diseases, tuberculosis, and HIV infection, are associated with an enhancement in the activity of ADA2, which can be used as a biomarker of the disease and response to treatment, especially in patients with tuberculosis [82][83][84][85]. It is reported that ADA2 can act as a growth factor [86].…”
Section: The Biological Significance Of Adenosine Deaminasementioning
confidence: 99%